Mobile Application with Augmented Reality and its Impact on Anatomy Learning in Human Medicine Students - Gutiérrez-Jara, Jéssica K.; Malpica-Rodríguez, Manuel E.; Pérez-Aguilar, Daniel A.; Pérez-Aguilar, Jair M. (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This paper presents the development of an augmented reality (AR) mobile application to display 3D structures of the human body and evaluate its impact on anatomy learning in students of the Faculty of Human Medicine of a university in northern Peru. The need to improve educational quality is addressed, given that traditional methods often lack adequate resources and effective motivation for students. Through the application, which uses the Mobile-D methodology, 3D anatomical models, a database, and a supporting web page were created. The results indicate that the AR mobile application had a positive impact on the learning of first-year Human Medicine students with a significant improvement of 0.88 in the averages, since it provides them with the basic knowledge for the introduction to this subject, in addition to improving their motivation and being considered as a learning and feedback tool.